2009
DOI: 10.1177/230949900901700231
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of the Unresurfaced Patella after Total Knee Arthroplasty: A Report of Two Cases

Abstract: Patellar fractures are unusual in total knee arthroplasty without patellar resurfacing. We present 2 such cases that occurred within postoperative 2 months and were managed conservatively. Both patients had their knee function preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…However, more recent advances in implant design to develop 'patella friendly' femoral components, which typically have a more anatomic geometry, with a deep patellar groove and more prominent lateral flange (Johnson et al, 2012), have resulted in clinical outcomes on par with those reported for resurfaced patellae (O'Brien et al, in press;Hooper et al, 2009;Chalidis et al, 2011). Several studies have reported higher incidences of anterior knee pain with an unresurfaced patella; Helmy et al (2003) calculated the probability of anterior knee pain as 12% and 26%, respectively, with and without resurfacing, while others claim greater risk of patellar fracture with resurfaced patellae, with fracture rates of 0.2%-20% in resurfaced and 0.05% in unresurfaced patellae reported (Dalury and Dennis, 2003;Seijas et al, 2009).…”
Section: Introductionmentioning
confidence: 91%
“…However, more recent advances in implant design to develop 'patella friendly' femoral components, which typically have a more anatomic geometry, with a deep patellar groove and more prominent lateral flange (Johnson et al, 2012), have resulted in clinical outcomes on par with those reported for resurfaced patellae (O'Brien et al, in press;Hooper et al, 2009;Chalidis et al, 2011). Several studies have reported higher incidences of anterior knee pain with an unresurfaced patella; Helmy et al (2003) calculated the probability of anterior knee pain as 12% and 26%, respectively, with and without resurfacing, while others claim greater risk of patellar fracture with resurfaced patellae, with fracture rates of 0.2%-20% in resurfaced and 0.05% in unresurfaced patellae reported (Dalury and Dennis, 2003;Seijas et al, 2009).…”
Section: Introductionmentioning
confidence: 91%
“…Fracture of patella was detected 1.5 years after TKA. Fracture of the patella occurred within 2 months in the case reported by Reed et al [2] and less than 3 years in the cases reported by Seijas Roberto et al [7]. Ortiguera et al [11] described that about 80% of patellar fractures occur within 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complications increase manifold with resurfacing which can be due to incorrect patellar tracking, metal component, uncemented component and patellar clunk syndrome; that too can cause fracture of patella or patellofemoral problems after TKA the percentage of which is quite high [1]. It is noteworthy to mention that involvement of extensor mechanism is the most common complication after TKA [1,7].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, patella fracture following revision TKA has a reported incidence ranging from 0.2% to 21% [10-13]. Ninety percent of these fractures occurred when the patella had been resurfaced (88%) often without specific trauma or significant symptoms [14-18]. Seijas et al [14] reported 2 cases of atraumatic non-resurfaced patella fracture following a primary TKA in 2009 highlighting that this was an extremely uncommon event.…”
Section: Introductionmentioning
confidence: 99%
“…Ninety percent of these fractures occurred when the patella had been resurfaced (88%) often without specific trauma or significant symptoms [14-18]. Seijas et al [14] reported 2 cases of atraumatic non-resurfaced patella fracture following a primary TKA in 2009 highlighting that this was an extremely uncommon event. Factors associated with atraumatic patellar fractures include patellar subluxation, improper patellar resection, vascular compromise, component designs and thermal necrosis [13,15].…”
Section: Introductionmentioning
confidence: 99%